Salicylic acid is involved in resistance responses in the Russian wheat aphid-wheat interaction - Mohase, Lintle; van der Westhuizen, Amie J. (Journal of plant physiology, 2002)
The effect of Russian wheat aphid (RWA), Diuraphis noxia (Mordvilko), infestation on the salicylic acid (SA) content and catalase (EC 1.11.1.6) activity were studied in resistant (cv. Tugela DN) and near-isogenic susceptible (cv. Tugela) wheat ( Triticum aestivum L.). The aim was to gain information on the involvement of SA in the resistance responses in wheat against the RWA. RWA infestation selectively induced SA accumulation and peroxidase (EC 1.11.1.7) activity in the resistant wheat. Catalase activity was, however, inhibited in both resistant and susceptible wheat plants. Intercellularly applied SA confirmed the possible inhibitory effect of SA on catalase and stimulating effect on defense responses as indicated by peroxidase used as a marker. Results suggest the involvement of SA in the resistance of wheat against the RWA. A SA inhibitable catalase is also present in wheat; indications are that it may not be involved in SA-mediated defence responses.